Associations of Dietary Fat Intake With Mortality From All Causes, Cardiovascular Disease, and Cancer: A Prospective Study - Yao, Xiaolin; Xu, Xin; Wang, Shuo; Xia, Dan (Frontiers in Nutrition, 2021)
Public concerns have been growing for the impact of fat intake on health. Existing evidence linking specific dietary fat intake with mortality is controversial. We aimed to investigate the association between fat intake and total and cause-specific mortality in the Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial. Intakes of saturated fatty acids (SFAs), trans-fatty acids (TFAs), monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) were assessed via food frequency questionnaires. The primary outcomes were total, cardiovascular disease (CVD) and cancer mortality. Multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression model adjusting for confounders. Overall, 24,141 deaths were recorded over a total 1,672,715 person-years of follow-up. There was a significant positive association between SFAs consumption and total mortality (HRQ5 vs. Q1 = 1.13, 95% CI 1.05-1.22; Pfor trend < 0.001). PUFAs intake was strongly inversely associated with total mortality (HRQ5 vs. Q1 = 0.79, 95% CI 0.73-0.85; Pfor trend < 0.001) and CVD mortality (HRQ5 vs. Q1 = 0.66, 95% CI 0.58-0.75; Pfor trend < 0.001). There was a similar, but to a lesser extent, association between MUFAs intake and total and CVD mortality (HRQ5 vs. Q1 0.91 (95% CI: 0.84-0.99), Pfor trend = 0.044 and 0.85 (0.73-0.98), Pfor trend = 0.020, respectively). None of these types of dietary fat were associated with cancer mortality (all Pfor trend > 0.05). In conclusion, this study observed a detrimental effect of SFAs intake on total mortality; in contrast, greater consumption of PUFAs and MUFAs were associated with lower risks of all-cause death and CVD mortality.